2021
DOI: 10.20467/humancaring-d-20-00022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Servant Leadership in Nursing: A Concept Analysis

Abstract: Despite the abundance of servant leadership literature, scholars recognize the need for a more precise conceptualization of the concept. Although the predominant literature emanates from organizational management and industry describing servant leadership as a theory, model, philosophy, or leadership style, less attention has focused on servant leadership in academia, and most notably in nursing. The purpose of this analysis is to clarify the concept of servant leadership and to provide further delineation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The sample population* was composed of seventeen conceptual papers and reviews (eg, Aij & Rapsaniotis, 20 Neville et al), 12 five qualitative (interview, case, and ethnographic) studies (eg, Sturm, 1 Vanderpyl), 38 thirty-two quantitative studies (eg, Hosseini et al), 39 and one study that employed a mixed methods design. 40 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample population* was composed of seventeen conceptual papers and reviews (eg, Aij & Rapsaniotis, 20 Neville et al), 12 five qualitative (interview, case, and ethnographic) studies (eg, Sturm, 1 Vanderpyl), 38 thirty-two quantitative studies (eg, Hosseini et al), 39 and one study that employed a mixed methods design. 40 …”
Section: Resultsmentioning
confidence: 99%
“… 45 Review papers presented servant leadership as a prominent model in healthcare 46 that enables employees to become effective lean leaders. 20 Moreover, a few conceptual papers 10 , 12 noted that servant leadership is not widely taught in healthcare leadership education programs.…”
Section: Resultsmentioning
confidence: 99%
“…As external, internal, and organizational drivers became apparent to SON executive leaders, we worked collaboratively to identify strategies. Using core principles of servant leadership as a guide (Simon, 2021), we focused on believing in the best in others while helping those served reach full potential (Neville et al, 2021). These strategies provided opportunities to strengthen the SON community and build resilience through risk-taking and action steps (see Supplemental Content for Table 1, available at http://links.lww.com/NEP/A369).…”
Section: Strategies and Outcomesmentioning
confidence: 99%
“…It was first propounded as ‘servant leadership’ (SL) by Robert K. Greenleaf in the 1970s [ 6 , 7 ]. Since then, the concept of SLM has been used extensively in much academic literature, especially in professions in which the professionals—that is, teachers, doctors, nurses, engineers, sports coaches, and athletes—play the dual roles of like servant and leader [ 4 , 8 , 9 , 10 , 11 , 12 ]. A plethora of studies on police officers can be found, with scholars arguing that the police play dual roles, depending on the situation; these roles include their positions as servants of the people and decision-making leaders [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%